Attitudes of the Community Daily Behavior in Television News As a Mirror of Civic Education (PKn) - Juliati Juliati (Budapest International Research and Critics University, 2021)
In this era of globalization, we as citizens of the world can experience technological developments where one country with another country can easily find out the strengths and weaknesses of a country along with advances in communication technology which greatly affect citizens. So that from year to year there have been many violations of the law because of the desire to enjoy the pleasures of very high technological advances. This illustrates the problem in which many residents are involved in violations that lead to crime. The solution is with civic education material that must be addressed so that it can adjust to the situation and avoid the negative influence of the very fast development of communication technology. While civic education is considered successful or not, it can be seen from the attitude of people's daily behavior through television news broadcasts, one of which is television news I News RCTI. Then the government can participate in controlling society to make it better (good citizenship). Apart from Civic Skills, Civic Virtues, and Civic Religion, the teaching and learning process must also be improved, including the arrangement of the material along with the teacher's way of teaching through methods, media and models. Since good citizens are not born instantly, but are in a series of interpersonal and intellectual abilities according to the times. The results that can be achieved are that television news must be studied by each individual and then apply the results of the good viewing materials based on that television news for the family, environment and the wider community.